1996
DOI: 10.1063/1.471299
|View full text |Cite
|
Sign up to set email alerts
|

Complex oscillations and global coupling during the catalytic oxidation of CO

Abstract: Rate oscillations during heterogeneous catalytic reactions often display self-similar mixed-mode oscillations that have also been found in various other experimental systems. Spatially nonuniform behavior is revealed by monitoring the surface temperature during complex oscillations in the kinetic regime of the CO oxidation on a Pd supported catalyst at atmospheric pressure. The experimental results demonstrate the influence of global coupling via the gas phase concentration of the deficient component. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Transient experiments with the variation of reaction mixture composition indicate that the high activity state is associated with the reduced catalyst, while the oxidized catalyst demonstrates low activity. The oxidation}reduction mechanism has been suggested earlier for kinetic oscillations, observed during CO oxidation over Pd (110) single crystal surface (Basset & Imbihl, 1990), Pd wire (Turner, Sales & Maple, 1981) and Pd zeolite catalysts (Jaeger, MoK ller & Plath, 1986;Slin'ko, Jaeger & Svensson, 1989;Liauw, Plath & Jaeger, 1996). The dependencies of the oscillatory amplitude and period on the reaction temperature and CO concentration observed in this study reveal the similar trends to the ones reported earlier for kinetic oscillations.…”
Section: Discussionsupporting
confidence: 77%
“…Transient experiments with the variation of reaction mixture composition indicate that the high activity state is associated with the reduced catalyst, while the oxidized catalyst demonstrates low activity. The oxidation}reduction mechanism has been suggested earlier for kinetic oscillations, observed during CO oxidation over Pd (110) single crystal surface (Basset & Imbihl, 1990), Pd wire (Turner, Sales & Maple, 1981) and Pd zeolite catalysts (Jaeger, MoK ller & Plath, 1986;Slin'ko, Jaeger & Svensson, 1989;Liauw, Plath & Jaeger, 1996). The dependencies of the oscillatory amplitude and period on the reaction temperature and CO concentration observed in this study reveal the similar trends to the ones reported earlier for kinetic oscillations.…”
Section: Discussionsupporting
confidence: 77%
“…This oscillatory behaviour is commonly perceived as a periodic transformation between the two different conversion levels of a bistable reaction. The bistable reaction is caused by nonlinear kinetics 12 , possibly in conjunction with mass transport 13,14 . The periodic transformation has been attributed to dynamic changes in the catalyst surface 12 .…”
mentioning
confidence: 99%
“…Globally coupled oscillatory systems have been studied both experimentally and theoretically in a variety of systems including chemical reactions [10,11,12,13,14,15], metabolic oscillators [16,17], electrochemical oscillators [18,19,20,21,22,23,24,25,26,27,28], catalytic reactions [29], neuronal networks [5,30,31,32,33,34,35], salt-water oscillators [36], laser arrays [37], and cardiac oscillators [38,39]. Theoretical studies have been performed using activator-inhibitor type models that explicitely describe the dynamics of the participating physical (chemical, biological, etc) variables.…”
Section: Introductionmentioning
confidence: 99%